The Underground Railroad - Messner, Kate; Hooks, Gwendolyn (Messner, Kate. History smashers., 2022)
"Through a mix of sidebars, illustrations, photos, and graphic panels, this book debunks myths about the Underground Railroad and Black Americans' struggle for freedom"--